2003
DOI: 10.1046/j.1442-2050.2003.00309.x
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of p53 protein expression and vascular endothelial growth factor expression in resected squamous cell carcinoma of the esophagus

Abstract: The most common genetic alterations found in a wide variety of cancers are p53 tumor suppressor gene mutations. p53 appears to be a nuclear transcription factor that plays a role in the control of cell proliferation, apoptosis, and the maintenance of genetic stability. Angiogenesis is a critical process in solid tumor growth and metastasis. Vascular endothelial growth factor (VEGF), a recently identified growth factor with significant angiogenic properties, may be a major tumor angiogenesis regulator. Few stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
24
0
1

Year Published

2004
2004
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 31 publications
(64 reference statements)
5
24
0
1
Order By: Relevance
“…This has been well established in previous studies conducted with nearly the same immunohistochemical procedures, together with a lack of correlation to prognosis, which is consistent with our findings (Sarbia et al, 1994;Hardwick et al, 1997;Shimada et al, 1999;Wang et al, 1999;Ahn et al, 2002;Rosa et al, 2003). P53 mutations are Diffuse EGFR staining and reduced overall survival L Gibault et al peculiarly frequent in high-SCCO incidence areas like Brittany (Audrezet et al, 1993), where we performed our study; some geographic specificity might also be implicated.…”
Section: P53 Protein In Sccosupporting
confidence: 92%
See 2 more Smart Citations
“…This has been well established in previous studies conducted with nearly the same immunohistochemical procedures, together with a lack of correlation to prognosis, which is consistent with our findings (Sarbia et al, 1994;Hardwick et al, 1997;Shimada et al, 1999;Wang et al, 1999;Ahn et al, 2002;Rosa et al, 2003). P53 mutations are Diffuse EGFR staining and reduced overall survival L Gibault et al peculiarly frequent in high-SCCO incidence areas like Brittany (Audrezet et al, 1993), where we performed our study; some geographic specificity might also be implicated.…”
Section: P53 Protein In Sccosupporting
confidence: 92%
“…Indeed, according to most of the available studies, VEGF expression significantly predicts a poorer survival (Inoue et al, 1997;Uchida et al, 1998;Koide et al, 1999Koide et al, , 2001Kato et al, 2002). On the contrary, some other recent reports (Ahn et al, 2002;Rosa et al, 2003) are consistent with our results, evidencing a lack of relationship between VEGF expression and clinical outcome in SCCO. Underneath this may prevail a difficulty in immunohistochemical interpretation of VEGF staining.…”
Section: Vascular Endothelial Growth Factor In Sccosupporting
confidence: 91%
See 1 more Smart Citation
“…However, p53 mutations do not appear to correlate with VEGF expression in prostate [35] and renal carcinomas [36] . Koide et al [17] reported that p53 expression correlated signifi cantly with MVD and VEGF protein expression in esophageal carci- noma, although there are several reports showing no correlation between these variables [37,38] . It is known that p53 regulates apoptosis [39] and that abnormal p53 expression decreases apoptosis [40] .…”
Section: Discussionmentioning
confidence: 99%
“…For example, tumors with deletion of both alleles of the gene would be classifi ed as negative, as would tumors that do not express p53, and interruption of normal degradation of p53 may result in nonmutational accumulation of p53 protein [49] . It has been suggested that the function of p53 is inactivated by other mechanisms, such as damage to components of the G1 phase of the cell cycle (p16, pRB and cyclin D1) [37,50] . Analysis of loss of function of the p53 protein would be necessary in addition to mutation analysis of the tumor cell DNA.…”
Section: Discussionmentioning
confidence: 99%